2020
DOI: 10.1155/2020/5080832
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea Polyphenols Modulated Cerebral SOD Expression and Endoplasmic Reticulum Stress in Cardiac Arrest/Cardiopulmonary Resuscitation Rats

Abstract: Background. Reducing cerebral ischemia-reperfusion injury is crucial for improving survival and neurologic outcomes after cardiac arrest/cardiopulmonary resuscitation (CA/CPR). The purpose of this study is to investigate the neuroprotective effects of green tea polyphenols (GTPs) concern with the modulation of endogenous antioxidation and endoplasmic reticulum stress. Methods. After subjecting to CA/CPR, rats were randomized into the saline group (NS, n = 40) and the GTPs group (GTPs, n = 40). Each group was b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…However, reperfusion processes after ischemic attack may further exacerbate brain damage, which is named cerebral ischemia/reperfusion (I/R) injury [5,6]. It is increasingly understood that multiple pathophysiological processes, includ-ing oxidative stress, the inflammatory response, neuronal death, and apoptosis, play a pivotal role in the development of cerebral I/R injury [7][8][9][10]. Thus, treatments based on the above mechanisms are proposed as a promising strategy to attenuate the outcomes of stroke and cerebral I/R injury.…”
Section: Introductionmentioning
confidence: 99%
“…However, reperfusion processes after ischemic attack may further exacerbate brain damage, which is named cerebral ischemia/reperfusion (I/R) injury [5,6]. It is increasingly understood that multiple pathophysiological processes, includ-ing oxidative stress, the inflammatory response, neuronal death, and apoptosis, play a pivotal role in the development of cerebral I/R injury [7][8][9][10]. Thus, treatments based on the above mechanisms are proposed as a promising strategy to attenuate the outcomes of stroke and cerebral I/R injury.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating literatures report that some agents with antioxidant properties have a neuroprotective role against ischemic stroke [ 11 13 ]. Similarly, our previous study indicated that antioxidative therapy exerted an effective role against CIRI in CA/CPR rat model [ 14 ]. Some studies on components of citric fruits support the antioxidant, anti-inflammatory, and antinecroptosis effects in several experimental models.…”
Section: Discussionmentioning
confidence: 64%
“…However, prolonged ERS triggers apoptosis, not directly, but by activating downstream proapoptotic molecules that push cells toward the death pathway. The expression of CHOP is of great significance in inducing prosurvival to proapoptosis [ 39 ]. PERK/eIF2 α /ATF4 pathway is the leading pathway for activation of CHOP among the three branches of UPR.…”
Section: Discussionmentioning
confidence: 99%